2021
DOI: 10.1055/a-1376-2394
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-directed transgastric ERCP (EDGE): a systematic review describing the outcomes, adverse events, and knowledge gaps

Abstract: Background and Aims: EUS-directed transgastric ERCP (EDGE) has emerged as a viable, completely endoscopic method for performing pancreaticobiliary interventions in patients with Roux-en-Y gastric bypass anatomy. The aims of this systematic review are: 1) to describe indications, outcomes and complications of EDGE; and 2) to identify deficiencies in our knowledge of important technical approaches and clinical outcomes. Patients and methods: A systematic review was conducted via comprehensive search of MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 33 publications
4
39
3
1
Order By: Relevance
“…A recent systematic review evaluated nine case series and eight case reports. In the case series, 169 patients underwent EDGE with a technical success rate of 99 % (168/169) for gastrogastrostomy/jejunogastrostomy creation and 98 % (166/169) for subsequent ERCP [184]. A recent study that compared LA-ERCP with EA-ERCP found both techniques to be similar with regards to technical success, AE rates, and procedure time [187] (Table 11 s).…”
Section: Key Question 22: What Are the Technical And Clinical Success Rates Of Edge?mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review evaluated nine case series and eight case reports. In the case series, 169 patients underwent EDGE with a technical success rate of 99 % (168/169) for gastrogastrostomy/jejunogastrostomy creation and 98 % (166/169) for subsequent ERCP [184]. A recent study that compared LA-ERCP with EA-ERCP found both techniques to be similar with regards to technical success, AE rates, and procedure time [187] (Table 11 s).…”
Section: Key Question 22: What Are the Technical And Clinical Success Rates Of Edge?mentioning
confidence: 99%
“…Stent maldeployment can be adequately managed by endoscopy in the large majority of cases, reducing the likelihood of severe AEs, such as peritonitis, and/or death [147,164,182]. Long-term AEs in patients with EUS-guided lumento-lumen anastomoses include stent migration [148,183,184], obstruction by food residue [148], and tissue ingrowth [180] or overgrowth [145].…”
Section: Key Question 20: What Are the Most Common Adverse Events Associated With Eus-ge?mentioning
confidence: 99%
See 2 more Smart Citations
“…I read with pleasure the systemic review of Prakash et al on the outcomes, adverse events, and knowledge gaps of endoscopic ultrasound (EUS)-directed transgastric endoscopic retrograde cholangiopancreatography (EDGE) [1]. EDGE was the first example of an EUS-directed entero-enteral anastomosis performed in a human using a lumen-apposing metal stent (LAMS) [2].…”
mentioning
confidence: 99%